Are You Sure About Your Career? Predictors of Vocational Confidence in Engineering Students - Marina Sousa; Alexandra R. Costa; Leandro S. Almeida; Eunice Fontão (Education Sciences)
The increasing flexibility and rapid, profound changes in the labor market require employability skills from graduates, dem1anding greater attention from higher education institutions to training opportunities that foster the development of these skills among their students. Using a sample of 373 first-year engineering students, this study analyzed, through regression analysis, the impact of sociodemographic (gender, age), academic (work, program choice, average grade), and psychological (life satisfaction, perseverance of effort, consistency of interests) variables on students’ confidence in achieving their professional career project after completing their degree. The results indicate that women and younger students show lower levels of confidence in achieving their future vocational projects, as do students with lower academic performance and those with less consistency in their interests. These findings suggest the need for specialized support services for students, starting from the first year, in career development provided by higher education institutions.